Culturally Responsive Humanistic Islamic Education among the Anak Dalam Indigenous Community - Darmawi, Darmawi; Warsah, Idi; Fakhruddin, Fakhruddin (Journal La Edusci, 2025)
This study explores the implementation of Islamic Religious Education within the Suku Anak Dalam communities of Bukit Duabelas by examining how a humanistic approach enables religious learning to unfold in ways that honor cultural identity and everyday lived experience. Using a qualitative case study design, the research draws on in depth interviews, participatory observations, and document analysis to understand how Islamic teachings are introduced, interpreted, and gradually internalized in communities shaped by semi nomadic movement, strong ancestral traditions, and an oral knowledge system. The findings reveal that religious learning emerges most meaningfully when educators adopt flexible and dialogical strategies such as storytelling, modeling, and culturally grounded conversations that align with the emotional pace and social rhythms of the community. These approaches allow Islamic values to intersect naturally with local wisdom related to solidarity, ecological ethics, and kinship obligations. The study also identifies persistent challenges, including low literacy levels, the enduring authority of adat, and limited access to formal educational resources, which require educators to negotiate teaching with sensitivity and patience. Despite these constraints, observable social transformations indicate growing familiarity with Islamic practice, particularly among children and women. The study concludes that a humanistic and culturally responsive orientation is essential for fostering inclusive and sustainable religious education in indigenous settings and contributes to broader discussions on the development of contextually grounded Islamic pedagogy in multicultural societies